Reputação corporativa sob a ótica da sustentabilidade e desempenho superior persistente de empresas de capital aberto - Cardoso, Vanessa Ingrid da Costa (2013)
The intensification of relations between the global markets presents a relevant reflection on organizations, so as to remain in the market, they need to further preserve and improve their image in front of their stakeholders. In this sense, the concept of reputation emerges, being often discussed in the context of organizations and moreover can be understood as the set of organizational attributes developed over time, which influences the way stakeholders perceive companies within the market. In this study, corporate reputation is examined from the perspective of sustainability and of its influence in the companies’ superior and persistent performance under the theory of signaling’s foundation. Empirical evidence reveals that socially responsible actions taken by companies provide them a favorable reputation, as they issue positive signals to the market, offering greater attractiveness to stakeholders since they perceive higher reliability and lower risks (Fombrun, Shanley 1990; Fombrun; RINDOVA, 1996; Fombrun, Van Riel 1997, SCHULTZ, Nielsen; BOEGE, 2002; GARDBERG; Fombrun, 2002; ROBERTS & Dowling, 2002; CAIXETA et al. 2011). By attracting and establishing their relationships with various stakeholders, the achievement of either sustainable competitive advantage or the superior persistent performance is assured in the market companies (Barney, 1991; TIERGARTEN; ALVES, 2008; HAIL JUNIOR; ALCALDE; COSTA, 2009). The scope of these previous studies on the topic did not allow analysis of the longevity of the benefits gained by neither good corporate reputation nor in differentiated market contexts. Within this context, this study aims at investigating the relationship between corporate reputation and superior persistent performance of public companies that publish sustainability reports, according to Global Reporting Initiative (GRI)’s listing. It is a descriptive and explanatory research of quantitative nature, using bibliographic and documentary procedures with the application of statistical tools Correspondence Analysis, Average Testing and Panel Analysis. The study’s justification is to seek to contribute on expanding the discussion on corporate reputation in the perspective of sustainability. Moreover, it presents a differentiated analysis for dealing with the issue relating to the superior persistent performance and checking whether corporate reputation relates to the achievement and maintenance of a competitive advantage for a long period of time. Anacor points out that companies with higher levels of reputation are included in the group of companies with higher performance. Moreover, the conducted average testing shows that companies with superior persistent performance regard a statistically different reputation from their counterparts without superior persistent performance, being that the former presented an average index of corporate reputation greater than the latter. The preliminarily performed panel data analysis indicated no association between corporate reputation and superior persistent performance, disproving the research hypothesis. However, by transforming the variables into factors and using them in the panel data analysis, a performance dependency relationship was identified regarding size (represented by its size) and credibility (represented by its debt and reputation) factors. Therefore, it is concluded that, for the sample considered in this research, reputation alone is not able to influence business performance, but taking debt into account; the credibility factor (grouping the reputation and debt factors) may provide further explanations about performance. Thus, according theory of signaling, the reputation represents signals to the market and it is able to influence the behavior of stakeholders, impacting their performance.